2020
DOI: 10.1101/2020.07.07.191742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Connexin 43 Carboxyl Terminal Mimetic Peptide αCT1 Prompts Differentiation of a Collagen Scar Matrix Resembling Unwounded Skin

Abstract: AbstractPhase II clinical trials have reported that acute treatment of surgical skin wounds with the therapeutic peptide αCT1 improves cutaneous scar appearance by 47% 9-months post-surgery – though mode-of-action remains unknown. Scar matrix structure in biopsies 2 to 6 weeks post-wounding treated topically with αCT1 or control treatments from human subjects, Sprague-Dawley rats, and IAF hairless guinea pigs were compared. The sole effect on scar structure in humans was that α… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Moreover, PI3K activation in this study triggered an interaction between α5β1-integrin and Cx43, resulting in the opening of Cx43 HCs. A recent study reporting in silico (computational and mathematical), ex vivo, and in vitro evidence of scar formation demonstrated that αCT1 may render cells insensitive to biomechanical inputs during scar differentiation [ 203 ]. Computational modeling predicted that αCT1′s alteration of collagen organization, resulting from its effects on fibroblast migration characteristics (as fibroblast secrete collagen), occurs in a mechanically-sensitive manner.…”
Section: Channel-independent Roles Of Cx43 In Barrier Functionmentioning
confidence: 99%
“…Moreover, PI3K activation in this study triggered an interaction between α5β1-integrin and Cx43, resulting in the opening of Cx43 HCs. A recent study reporting in silico (computational and mathematical), ex vivo, and in vitro evidence of scar formation demonstrated that αCT1 may render cells insensitive to biomechanical inputs during scar differentiation [ 203 ]. Computational modeling predicted that αCT1′s alteration of collagen organization, resulting from its effects on fibroblast migration characteristics (as fibroblast secrete collagen), occurs in a mechanically-sensitive manner.…”
Section: Channel-independent Roles Of Cx43 In Barrier Functionmentioning
confidence: 99%
“…In some of these tissues, matrix structure and the resulting mechanical properties vary significantly across local subregions, and the effects of such heterogeneity can be important for tissue function or failure. For example, mechanical stress gradients have been shown to produce heterogeneous structural hallmarks during headfold morphogenesis [6,7]; a hammock-like heterogeneity of matrix orientation from commissure to commissure in heart valves has been a key target of tissue engineering approaches [8,9]; the spatial transition from highly aligned tendon matrix to randomly oriented and mineralized bone matrix at the tendon-bone enthesis is critical to proper load transfer and musculoskeletal function [10,11]; spatial heterogeneity in the structural composition of aneurysms has been associated with high variation in tensile moduli and failure locations [12,13]; and collagen orientation heterogeneity in dermal wounds has been associated with improved cell infiltration and healing rates [14].…”
Section: Introductionmentioning
confidence: 99%